Teaching orientations of freshman pre-service science teachers - Güven, Devrim; Muğaloğlu, Ebru Z.; Doğança-Küçük, Zerrin; Cobern, William W. (Journal of Turkish Science Education, 2019)
The aim of this exploratory research is to understand teaching orientations of freshman pre-service science teachers and their rationales for those orientations. Through a mixed method, the current study collected quantitative (Pedagogy of Science Teaching Test) and qualitative (semi-structured interviews) data to deepen and analyze the research. The sample of the quantitative part in the study consisted of 143 freshman pre-service science teachers (122 females and 21 males) purposefully drawn from a state university in Turkey. To understand their rationales of their teaching orientation preferences, semi-structured interviews were conducted with fourteen interviewees, who held varying science teaching orientations. The findings of this research showed that the freshman pre-service science teachers had a variety of orientations that were not influenced by their earlier science learning experiences. Also, the results indicated that the orientations were largely related to the freshman pre-service science teachers‟ conceptions of „roles of teachers and students, students‟ grades and nature of subject matter‟ rather than their immediate experiences as learners. The current study recommends that these conceptions should be adressed in the teacher education programs with appropriate experiences that engage pre-service teachers to critical reflection throughout the teacher education program.
Keywords: PCK; preservice science teachers; teaching orientations